REKONSTRUKSI IDENTITAS ETNIK: SEJARAH SOSIAL POLITIK ORANG PAKPAK DI SUMATERA UTARA 1958 - 2003 - Budi Agustono (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
This dissertation aims to analyze the history of the Pakpak people who havebeen marginalized politically, economically and culturally in the midst ofToba Batak domination since their settlement in Pakpak between the early20th to early 21st centuries. The result of the research indicates that power maynot only defne and revitalize identity, but it is also capable of constructingidentity. The reconstruction of ethnic identity may occur because in additionto the existing defnition of ethnicity, customary laws and tradition, there isan opportunity for the Pakpak elite to use their power to manipulate ethnicsentiment.Keywords: identity, power, Pakpak, and North Sumatera